Accuracy of sentinel lymph node mapping in detecting occult neck metastasis in papillary thyroid carcinoma - Steck,Jose Higino (2018)
ABSTRACT Objectives: The objectives of this study were to evaluate the following: 1) the accuracy of sentinel lymph node mapping (SLNM) in detecting metastasis in papillary thyroid carcinoma (PTC), and 2) if SLNM could modify the American Joint Committee on Cancer (AJCC) staging of previous cN0 PTC patients. Subjects and methods: Forty SLNM were performed prospectively in 38 consecutive cN0 PTC patients, with total thyroidectomy and elective compartment neck dissection (CND). The results of SLNM were compared with CND pathological findings to verify the accuracy of sentinel SLNM. Results: The mean patients’ follow-up was 36 months. A total of 133 SLN were found at levels VI, II, III and IV. The SLN was identified in 95% of the patients with one false negative, 95% sensitivity, a 94% negative predictive value and 97% accuracy. The SLNM upstaging from cN0 to pN+ was 49%, and to stages III and IVa, it was 21%. Conclusions: For this series of cN0 PTC patients: 1) SLNM accuracy was 97%, and 2) SLNM upstaging from cN0 to pN+ was 49%, whereas to stages III and IVa, it was 21%.